Genetic Characterization of a Streptococcus mutans LraI Family Operon and Role in Virulence - Kitten, Todd (American Society for Microbiology, 2000)
Proteins belonging to the LraI (for “lipoprotein receptor antigen”) family function as adhesins in several streptococci, as a virulence factor for endocarditis in at least one of these species, and potentially as metal transporters in many bacteria. We have identified and characterized the chromosomal locus containing the LraI family gene (designated sloC) from Streptococcus mutans, an agent of dental caries and endocarditis in humans. Northern blot analysis indicated that sloC is cotranscribed with three other genes. As with other LraI operons, the sloA and sloB genes apparently encode components of an ATP-binding cassette transport system. The product of the fourth gene, sloR, has homology to the metal-dependent regulator from Corynebacterium diphtheriae, DtxR. A potential binding site for SloR was identified upstream from the sloABCR operon and was conserved upstream from LraI operons in several other streptococci. Potential SloR homologs were identified in the unfinished genomic sequences from two of these, S. pneumoniae and S. pyogenes. Mutagenesis of sloC in S. mutans resulted in apparent loss of expression of the entire operon as assessed by Northern blot analysis. The sloC mutant was indistinguishable from its wild-type parent in a gnotobiotic rat model of caries but was significantly less virulent in a rat model of endocarditis. Virulence for endocarditis was restored by correction of the sloC mutation but not by provision of the sloC gene in trans, suggesting that virulence requires the expression of other genes in the sloC operon.